The Role of Higher Education in Developing Student Entrepreneurial Capabilities - Budiman, Agus; Hufad, Achmad; Wahyudin, Uyu; Akhyadi, Ade Sadikin; Sutarni, Nani; Rahmat, Abdul (International Journal of Psychosocial Rehabilitation, 2020)
Entrepreneurship in the context of the development of art education tourism programs in higher education is a serious concern that is able to reflect the role of universities in developing tourism tourism industry as an innovation and creativity of universities to improve the competitiveness of higher education goals through the development of entrepreneurship in the field of educational tourism. This paper discusses the role of tertiary institutions in developing educational tourism entrepreneurship which in its implementation empowers potential students to be given entrepreneurship training in order to be able to manage art education tourism programs events developed at tertiary institutions. The data was obtained from the results of the test instrument questions and questionnaire instruments given to 30 students at the Indonesian University of Education who were involved in the activities of entrepreneurial training programs in the management of tourism education through art. business that was built together with university stakeholders as well as government and non-government institutions.